Regulasi Kejahatan Cyber Sebagai Upaya Pertanggungjawaban Pelaku Tindak Pidana Cybersquatting - Dewi Muti’ah; Firda Laily Mufid (Universitas Merdeka Madiun, 2022)
Abstract—It’s undeniable that the emergence of the internet is like a double-edged sword, on the one hand it has a positive impact and on the other it has a negative impact. The positive impact of the internet is that we can get various information around the world easily. Misuse of domain names has led to a new crime in the cyber world, namely cybersquatting. Criminals take advantage of well-known domain names by making duplicates of those domain names which then register them for resale to other parties at a higher price. This article uses normative legal research, meaning that the issues raised, discussed and described in this research are focused on applying the rules or norms in positive law. This type of normative juridical research is carried out by examining various kinds of formal legal rules such as laws, literatures that are theoretical concepts which are then related to the problems that are the subject of discussion. The results obtained from writing this article are that regulations regarding cyber regulation in Indonesia are not only regulated in KUHP but also regulated in Undang-undang Republik Indonesia Nomor 19 Tahun 2016 tentang Perubahan Atas Undang-undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik and that regulations regarding cyber in Indonesia have not yet reached cybersquatting crime.. The current ITE Law is in fact still unable to realize criminal responsibility for cybersquatting perpetrators.